A novel insight into the anticancer mechanism of metformin in pancreatic neuroendocrine tumor cells. (1st June 2020) - Vitali, E.; Boemi, I.; Piccini, S.; Tarantola, G.; Smiroldo, V.; Lavezzi, E.; Brambilla, T.; Zerbi, A.; Carnaghi, C.; Mantovani, G.; Spada, A.; Lania, A.G.
Abstract: The antidiabetic drug metformin displays anticancer properties in several neoplasms. In pituitary NETs, aryl hydrocarbon receptor-interacting protein (AIP) is up-regulated by the somatostatin analog octreotide. Metformin inhibited QGP-1 cell proliferation in a dose- and time-dependent manner, at concentrations similar to those achievable in treated patients (−31 ± 12%, p < 0.05 vs basal at 100 μM). Moreover, metformin decreased pancreatic neuroendocrine tumors (PAN-NETs) cell proliferation (−62 ± 15%, p < 0.0001 vs basal at 10 mM), without any additive effect when combined with octreotide. Both octreotide and metformin induced AIP up-regulation. AIP silencing abolished the reduction of mTOR phosphorylation induced by metformin and octreotide. Moreover, metformin decreased HSP70, increased Zac1 and AhR expression; these effects were abolished in AIP silenced QGP-1 cells. In conclusion, metformin acts as an anticancer agent in PAN-NET cells, its activity is mediated by AIP and its interacting proteins. These findings provide a novel insight into the antitumorigenic mechanism of metformin. Highlights: Metformin acts as an anticancer agent in PAN-NET cells. AIP interacts with HSP70, AHR and Zac1. Metformin action is mediated by AIP and its interacting proteins.